Normal pattern and physiological significance of mitral valve flow velocity recorded using transseptal directional Doppler ultrasound catheterization. Issue 3 (March 1975) - Kalmanson, D; Bernier, A; Veyrat, C; Witchitz, S; Savier, C H; Chiche, P
Abstract : In 10 cardiac patients in whom an organic lesion of the mitral valve was exluded by standard investigation procedures during which a diagnostic transseptal catheterization for pressure measurements in the left heart was performed, the authors placed a directional Doppler ultrasonic catheter tip velocimeter at the site of the mitral ring and recorded the mitral flow velocity traces. The pattern of these normal curves is presented and a physiological interpretation proposed. The relation between the mitral flow velocity and low volume curves is discussed in the light of present experimental data on mitral valve flow velocity profiles and variations in size of the mitral orifice. The authors concluded that the flow velocity curves obtained by the Doppler technique constitute a valid physiological reference system for the study of the mitral valve flow velocity tracings that can be recorded in the various forms of mitral valve disease.